Protective Action of Antioxidants on Hepatic Damage Induced by Griseofulvin - M. del C. Martinez; S. G. Afonso; A. M. Buzaleh; A. Batlle (The Scientific World Journal)
Erythropoietic protoporphyria (EPP) is a disease associated with ferrochelatase deficiency and characterized by the accumulation of protoporphyrin IX (PROTO IX) in erythrocytes, liver, and skin. In some cases, a severe hepatic failure and cholestasis were observed. Griseofulvin (Gris) develops an experimental EPP with hepatic manifestations in mice such as PROTO IX accumulation followed by cellular damage as wells as necrotic and inflammatory processes. The antioxidant defense system was also altered. The aim was to evaluate the possible protective effect of different antioxidant compounds: trolox (Tx), ascorbic acid (Asc), the combination Tx and Asc, melatonin (Mel), and the polyphenols: ellagic acid, quercetin, chlorogenic acid, caffeic acid, gallic acid, and ferulic acid on liver damage and oxidative stress markers in a mouse model of EPP. Coadministration of Gris with Tx, Asc, and its combination, or Mel mainly affected heme biosynthetic pathway, resulting in a decrease in ALA-S activity which was increased by Gris, while the tested polyphenols exerted a protective effect on oxidative stress, decreasing lipid peroxidation and the activity of some antioxidant enzymes. In conclusion, antioxidant compounds can only protect partially against the liver damage induced by Gris, reducing oxidative stress or acting on heme regulation.